Pure Piezoelectricity Generation by a Flexible Nanogenerator Based on Lead Zirconate Titanate Nanofibers - Lee, Horim; Kim, Hoyeon; Kim, Dong Young; Seo, Yongsok (ACS omega, 2019)
Lead zirconate titanate (PbZr0.52Ti0.48O3, PZT) alloys have been extensively studied to be used for piezoelectric nanogenerators to harvest energy from mechanical motions. In this study, PZT nanofiber-based nanogenerators were fabricated to test their true piezoelectric performance without the triboelectric effect. Aligned PZT nanofibers were fabricated by a sol–gel electrospinning process. The thickness, area, and orientation of the PZT textile made by electrospinning a PZT solution onto multipair metal wires or metal mesh were controlled to form a composite textile. After the calcination, the PZT textile mixed with polydimethylsiloxane was placed between two flexible indium-doped tin oxide–polyethylene naphthalate substrates. The performance parameters of the nanogenerators were investigated under the bending motion, which excludes the triboelectric effect. An assembled nanogenerator of an area of 8 cm2 and a thickness of 80 μm could generate an electrical output voltage of 1.1 V and a current of 1.4 μA under the bending strain. The piezoelectric voltage depended on the thickness of the PZT textile, whereas the piezoelectric current depended on both the thickness and the area of the PZT textile. The electrical performance of the device was significantly affected by the orientation of the PZT fiber and the bending direction. The output voltage and the output current were strain-dependent, whereas the total integrated charge was independent of the strain rate. The properties of the flexible nanogenerator could be quantified to verify the pure piezoelectric performance of the device.